Heavy Metal Levels from some Biomass Emissions in Indoor Environment of selected Kitchens in Jos, Nigeria - O. F. Anjorin; L. C. Imoh; C. Uhunmwangho (Iranica Journal of Energy and Environment, 2024)
Since actual metal emissions can be assessed using Particulate matter (PM) as a proxy, monitoring and controlling metal compounds in biomass emissions is essential for determining their quantities and potential health effects. Using a low volume respirable dust sampler, indoor ambient metal-bearing particles were quantified in-situ and collected from nine (9) randomly selected public kitchens of boarding secondary schools in Jos, Plateau State. Atomic absorption spectrometry (AAS) was used to determine the amounts of specific heavy metals in these collected samples. Additionally, 114 responders' blood samples underwent a biochemical lead assay study. The mean concentrations of the samples taken for Mn, Cd, Cu, Fe, Cr, Zn, Ni, Pb, and Co were 0.097, 0.015, 0.254, 0.314, 1.027, 0.000, 0.076, 0.106, and 0.169 µg/m3, respectively. The results of the blood lead assay analysis showed that 54% of the subjects had B-Pb levels above 80 µg/dL, 33% had B-Pb levels between 40 µg/dL and 80 µg/dL, 8% between 25 µg/dL and 40 µg/dL, 4% between 10 µg/dL and 25 µg/dL, 4% below 10 µg/dL, and 15% below 10 µg/dL. In general, elevated levels of metal-bearing particles in the indoor environment public kitchens expose kitchen staff to several occupational hazards.